LAS ESPECIES CHILENAS DE CENTRIS (WAGENKNECHTIA) MOURE 1950 (HYMENOPTERA: APIDAE) - Vivallo, Felipe; Zanella, Fernando; Toro, Haroldo (Acta Entomológica Chilena, 2022)
A revisión of the Chilean species of the genus Centris (Wagenknechtia) is presented. The following species were included: C. cineraria cineraria Smith, C. cineraria neoqueenensis Friese, C. escomeli Cockerell, C. moldenkei Toro & Chiappa, C. orellanai Ruiz and C. rhodophthalma Pérez, with the description of the male of C. cineraria cineraria and C. orellanai. Floral records, distribution and biological notes are given for all the species included, with keys for the subgenera present in Chile and for the Chilean species of the subgenus Wagenknechtia.